Zainab Al-Ghazali: A History of Mujahidah Awakening in Egypt - Ghazali, Ummi Zainab Mohd; Sabjan, Muhammad Azizan (European Publisher, 2019)
Islamic civilization has given birth to the myriad of Muslim intellectuals regardless of gender. Zainab al-Ghazali was the founder of Muslim Women Association (MWA) of ‘Jama’at al-Sayyidat al-Muslima’ and the driving force behind Muslimah Akhwat Association. The basis of her thinking was on women’s right and place in Islam. The rallying call of her struggle was to spread Islamic knowledge towards Muslim women, instilling them with true Islamic principle of their rights and responsibilities, imparting a wave of change on them in line with the teaching of al-Quran and sunnah. Her approach towards spreading her da’wah was through written articles and lectures especially concerning women’s right and status in Islam. Her enlightenment had greatly impacted a massive number of women in Egypt to rise up to defend and to fight for their rights. Her personality, bravery, and intellectual have succeeded in uplifting the hierarchy of women in the world of da’wah and Islamic politics. She successfully warded off conventional prejudice towards women’s leadership in Islamic society. Her battle to define women’s role in Islamic society was truly exemplary and could be used as a point of reference towards women’s plight in society today.